Examining the Relationship of Personality Functioning and Treatment Completion in Substance Misuse Treatment - Fivos E. Papamalis (SAGE Publishing, 2020)
Background: Treatment retention is a major factor contributing to favourable outcome in the treatment of substance misuse, but the literature remains very limited. Despite evidence of the association of personality with drug use experimentation and relapse, surprisingly little is known about its role in the treatment process. Clients' personality functioning as measured by malleable and context sensitive characteristic adaptations in treatment are of concern. Aims: This study examines whether, and to what extent, personality functioning contributes to or hinders treatment completion. This paper examined the extent to which service users' characteristic adaptations may be potential determinants of treatment completion. Methodology: A longitudinal multi-site design was utilised, examining the therapy process in a naturalistic setting in five inpatient treatment units. The study examined whether service users' characteristic adaptations (SIPP-118) predict completion, while controlling psychosocial, motivational and treatment engagement indicators involving n = 340 participants from 5 inpatient centres. Multivariate regression analyses were applied to examine the predictive role of characteristic adaptations on treatment completion. Results: Findings indicated that certain dysfunctional characteristic adaptations emerged as strong predictors of treatment completion. Dysfunctional levels on Self-control and Social concordance were significant predictors of drop out from treatment. Individuals with low capacity to tolerate, use and control one's own emotions and impulses were almost three times more likely to drop-out compared to those without [OR] = 2.73, Wald = 6.09, P = .014, 95% CI [1.2, 6.0]. Individuals with dysfunctional levels on the ability to value someone's identity, withhold aggressive impulses towards others and work together with others were 2.21 more times more likely to complete treatment [OR] = 2.21, Wald = 4.12, P = .042, 95% CI [1.0, 4.7]. The analysis at the facet level provided additional insight. Individuals with higher adaptive levels on Effortful Control were 46% more times likely to complete treatment than the group [OR] = 4.67, Wald = 10.231, P = .001, 95% CI [1.81, 12.04], 47% more likely on Aggression regulation [OR] = 4.76, Wald = 16.68, P < .001, 95% CI [2.1, 10.3], and 26% more likely on Stable self-image [OR] = 2.62, Wald = 6.75, P < .009, 95% CI [0.9, 3.0]. Conclusions: These findings extend our knowledge of the predictive role of characteristic adaptations in treatment completion and highlight the clinical utility of capturing these individual differences early on. Delineating the role of characteristic adaptations in treatment may provide the basis for enhancing treatment effectiveness through individualized interventions that are scientifically driven and may open new avenues for the scientific enquiry of personality and treatment.